2011
DOI: 10.1177/1359105311398682
|View full text |Cite
|
Sign up to set email alerts
|

Chronic idiopathic urticaria and anxiety symptoms

Abstract: Chronic idiopathic urticaria (CIU) is a frequently disabling disease with a negative influence on the quality of life, and can cause psychopathological symptoms, such as anxiety. Our aim is to study further anxiety symptoms on CIU patients. Both CIU patients and the control group were studied by means of validated scales for psychopathology symptoms, psychological variables and quality of life. In this study, we reported high levels of anxiety symptoms. We found statistically significant correlations between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 28 publications
7
50
3
3
Order By: Relevance
“…According to other studies recording a decrease in the rate of alexithymia from childhood to adolescence (Gatta et al, 2011) and from early to mid adolescence (Joukamaa et al, 2007), this may be considered consistent with the gradually improving cognitive skills relating to emotion processing. This is the first study, as far as we know, investigating alexithymia among food-allergic patients; results are in line with studies on other atopic diseases (Baiardini et al, 2011b;Barbosa et al, 2011;Feldman et al, 2002;Maniaci et al, 2006), confirming an association between allergy and affect regulation. Alexithymia is not only an internal state but also associated with health outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…According to other studies recording a decrease in the rate of alexithymia from childhood to adolescence (Gatta et al, 2011) and from early to mid adolescence (Joukamaa et al, 2007), this may be considered consistent with the gradually improving cognitive skills relating to emotion processing. This is the first study, as far as we know, investigating alexithymia among food-allergic patients; results are in line with studies on other atopic diseases (Baiardini et al, 2011b;Barbosa et al, 2011;Feldman et al, 2002;Maniaci et al, 2006), confirming an association between allergy and affect regulation. Alexithymia is not only an internal state but also associated with health outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…However, taking into account the scale interpretation, it appeared that 15 people reported depressive symptoms (10 individuals evaluated them as mild, 4 as severe and 1 as very severe). Studies of the other researchers [4, 11, 13, 37–39] confirmed a higher depression level in CU patients. Moreover, recent literature data indicate that adolescents who suffer from non-infectious urticaria are at a higher risk of developing major depression [41].…”
Section: Discussionmentioning
confidence: 73%
“…CIU is not life-threatening, but has been demonstrated to have a substantial impact on the physical and psychological health of patients (5,6). Furthermore, symptoms last more than five years in up to 14% of patients, which suggests a long-term impact of this disorder (7) In the National Health and Wellness Survey (NHWS), United States and European patients with CU (survey did not evaluate CIU) treated with prescription medications were found to have substantially lower health-related quality of life (HRQL), greater work impairment and a greater prevalence of depression, anxiety and sleep problems when compared with matched controls who never experienced CU (8,9).…”
Section: Introductionmentioning
confidence: 99%